Achieving biogas production and efficient pollutants removal from nitrogenous fertilizer wastewater using combined anaerobic digestion and autotrophic nitrogen removal process. (November 2021) - Zhang, Xiaojing; Zhang, Hongli; Chen, Zhao; Wei, Denghui; Song, Yali; Ma, Yongpeng; Zhang, Hongzhong
Highlights: Biogas production from nitrogenous fertilizer wastewater was achieved. The total nitrogen removal from nitrogenous fertilizer wastewater reached 96.3%. The organics removal from nitrogenous fertilizer wastewater reached 98.4%. Enzyme activities and microbial abundance decreased when treated actual wastewater. Partial denitrification was integrated with autotrophic nitrogen removal process. Abstract: Nitrogenous fertilizer was massively utilized during agricultural production process, which led to the discharge of large amount of nitrogenous wastewater with low C/N ratio. In this study, anaerobic digestion combined with subsequent Completely autotrophic nitrogen removal over nitrite (CANON) process was adopted for treating nitrogenous fertilizer wastewater. The reactor performances and the microbial community structure were analyzed. Results showed that COD was mainly removed by anaerobic digestion, with the COD removal efficiency as 98.4%, and nitrogen was effectively removed via CANON integrating with partial denitrification, with the removal efficiency as 96.3%. The COD, ammonia and total nitrogen in the effluent of the combined process were 3.7, 2.9 and 7.4 mg L −1, respectively. Methanothrix (43.2%) and Methanomassiliicoccus (34.0%) were detected as the dominant methane production archaea, while Nitrosomanas (10.4%), Candidatus Kuenenia (13.8%) and Truepera (2.8%) were detected as the functional bacteria for nitrogen removal, when treated the nitrogenous fertilizer wastewater.